2014
DOI: 10.1002/app.41764
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of clay–TiO2 nanocomposite thin films with barrier and photocatalytic properties for food packaging application

Abstract: In this study, low-density polyethylene (LDPE) nanocomposite films with two types of nanoparticles, TiO 2 (3 wt %) and Closite 20A (3 and 5 wt %), were prepared using a melt blow extrusion as an industrial method and their properties such as mechanical properties, water vapor, oxygen and carbon dioxide gas barrier, and antimicrobial activity were tested. Transmission electron microscopy (TEM) and X-ray diffraction (XRD) were also performed to determine the degree of dispersion and exfoliation of nanoparticles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…The method for developing clay nanocomposite PE‐based film (5% nanoclay) with specific physicochemical properties was reported in the work of Bodaghi, Mostofi, Oromiehie, Ghanbarzadeh, and Ghasimi Hagh (). In this study, Water Vapor Transmission Rate (WVTR) was measured with a tester, model L80–500, equipped with a very sensitive and reliable humidity sensor, directly located in the measuring chamber to control temperature and relative humidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method for developing clay nanocomposite PE‐based film (5% nanoclay) with specific physicochemical properties was reported in the work of Bodaghi, Mostofi, Oromiehie, Ghanbarzadeh, and Ghasimi Hagh (). In this study, Water Vapor Transmission Rate (WVTR) was measured with a tester, model L80–500, equipped with a very sensitive and reliable humidity sensor, directly located in the measuring chamber to control temperature and relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…The method for developing clay nanocomposite PE-based film (5% nanoclay) with specific physicochemical properties was reported in the work of Bodaghi, Mostofi, Oromiehie, Ghanbarzadeh, and Ghasimi Hagh (2015). In this study, Water Vapor Transmission Rate (WVTR)…”
Section: Preparation and Characterization Of Nanocomposite Packaginmentioning
confidence: 99%
“…When incorporated into chitosan films, titanium oxide nanoparticles (TiO 2 NPs) made them active against G(−) and Gram‐positive (G(+)) bacteria as well as fungi, extending microbial stability of grapes . The photocatalytic activity of TiO 2 NPs was explored not only for antimicrobial purposes, but also for ethylene scavenging effects, which is useful to delay ripening of climacteric fruits. Migration studies indicated no detectable Ti in bread (food model) after a 6‐month contact with soybean polysaccharide films containing up to 7% TiO 2 NPs…”
Section: Inorganic Antimicrobial Nanostructuresmentioning
confidence: 99%
“…The control of the effects of oxidation by the incorporation of light‐blocking additives is key to the protection of the chemical structure of the polymer and in the design of materials to ensure long‐term properties . The protection of polymers against UV–vis photoirradiation is still a current issue, despite the extended use of organic and inorganic UV blockers .…”
Section: Introductionmentioning
confidence: 99%